Some aspects of allogeneic stem cell transplantation in patients with myelodysplastic syndrome: advances and controversy - Blau O (Dove Medical Press, 2014)
Olga Blau, Igor Wolfgang Blau Department of Hematology, Oncology and Tumor Immunology, Charité – Universitätsmedizin Berlin, Berlin, Germany Abstract: Myelodysplastic syndrome (MDS) is a heterogeneous group of myeloid disorders. MDS remains a disease of elderly patients; moreover, the incidence of high risk MDS is proportionally greater in elderly patients, with increased frequency of secondary acute myeloid leukemia, as well as adverse cytogenetic abnormalities. Allogeneic stem cell transplantation is a therapeutic approach with known curative potential for patients with MDS that allows the achievement of long-term disease control. Numerous controversies still exist regarding transplantation in MDS: timing of transplantation, disease status at transplantation and comorbidity, conditioning intensity, pretransplant therapy, and stem cell source. Various transplant modalities of different intensities and alternative donor sources are now in use. Current advances in transplant technology are allowing the consideration of older patients. This should result in a greater number of older patients benefiting from this potentially curative treatment modality. Despite advances in transplantation technology, there is still considerable morbidity and mortality associated with this approach. Nevertheless, with the introduction of reduced-intensity conditioning and thereby reduced early mortality, transplant numbers in MDS patients have significantly increased. Moreover, recent new developments with innovative drugs, including hypomethylating agents, have extended the therapeutic alternatives for MDS patients. Hypomethylating agents allow the delay of allogeneic stem cell transplantation by serving as an effective and well-tolerated means to reduce disease burden. Keywords: myelodysplastic syndrome, allogeneic stem cell transplantation, reduced-intensity conditioning